Band gap study of polyaniline and polyaniline/MWNT nanocomposites with in situ polymerization method - Almasi, M.J.; Fanaei Sheikholeslami, T.; Naghdi, M.R. (Composites. Part B, Engineering, 2016)
Polyaniline Emeraldine Bases (EBs) and EB incorporated with multiwall carbon nanotube (EB/MWNT) were synthesized using in situ chemical polymerization technique. The chemical and electrical properties of prepared samples were studied using various physical and electrical methods such as Fourier Transform Infrared (FTIR) spectroscopy, Scanning Electron Microscopy (SEM), X-ray Diffraction (XRD), UV–visible spectroscopy (UV–vis) and four point probe measurement technique. The FTIR spectroscopy is used to obtain the composition of the synthesized materials, while the SEM micrograph and XRD pattern indicates polymerization quality and the crystallization degree of the samples. The results show that the polymerization of aniline monomer is occurred on the surface of MWNT and the crystallization degree of EB does not vary when it subjects to formation of nanocomposite. By adding of MWNT the electrical conductivity of nanocomposite increases by 10 times compare to the pure polyaniline. From the UV–vis spectroscopy measurements, the optical band gap energy of EBs and nanocomposite is calculated for different produced samples. It is seen that treating EB by 20 mg MWNT improves the band gap of nanocomposite. It is deceases from 3 to 2.84 eV. By increasing the amount of MWNT, the band gap energy was gradually raised and became steady at 2.9 eV. Results indicate that the nanocomposite of EB/MWNT is more suitable for solar cell application because of higher electrical conductivity and lower band gap comparing to EB polymer.